Multi-objective optimization design of ship propulsion shafting based on response surface methodology-genetic algorithm - Cong, Zhang; Bingnan, Shu; Jiangtao, Zhang; Yong, Jin (Scientific Insights and Discoveries Review, 2024)
In order to reduce the power loss of the transmission equipment of the ship during navigation, improve the transmission efficiency of the propulsion shaft system, and improve the vibration performance of the shaft system, a multi-objective optimization design of a ship shaft system test bench was carried out based on the response surface model and genetic algorithm. The CCD star point design method was used to select reasonable experimental points in the optimization design space, and the response surface model of the minimum total power consumption and vibration response amplitude was fitted and constructed. Based on the genetic algorithm, the Pareto optimal solution of the regression function of the response surface model was solved by Matlab software. Several groups of optimization results were compared and analyzed to obtain the best optimization design scheme. The research results show that this combined method reduces the power loss of the shaft system by about , can effectively improve the transmission efficiency of the shaft system, reduce the vibration amplitude of the shaft system , and effectively suppress the vibration problem of the propulsion shaft system, thereby verifying the correctness and feasibility of the multi-objective optimization method of the ship propulsion shaft system.